Analisis Etika Pemasaran Syariah dalam Pengelolaan Usaha Franchise Gen Z (Studi Kasus pada Usaha Es di Indonesia di Jl. Sukawati Kabupaten Bone) - Silvianti. S; Muhammad Yamin; Rahma Hidayati Darwis (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research aims to analyze and describe the implementation of Islamic marketing ethics in the management of franchise businesses operated by Generation Z, with a case study on Es Teh Indonesia business located on Jl. Sukawati, Bone Regency. The approach used is qualitative with field research methods. Primary and secondary data were obtained through in-depth interviews with owners and employees, direct observation of business activities, and analysis of internal documents. Data validity was strengthened through source and method triangulation techniques. The research results show that Es Teh Indonesia business has implemented Islamic marketing ethics in a real and structured manner. The principle of Tauhid (Unity) is manifested through the use of halal raw materials, price transparency, avoidance of riba (usury), and awareness of paying zakat. The principle of Honesty is evident in information transparency, acknowledgment of mistakes, and prompt and appropriate handling of customer complaints. The principle of Acting Fairly is reflected in equal treatment of customers and employees, consistent pricing, and stakeholder involvement in decision-making. The principle of Serving with Humility is reflected in the friendly, polite, and solution-oriented attitude of employees in providing services. The implementation of these four principles of Islamic marketing ethics is not applied partially, but is functionally integrated in all aspects of franchise business management, including planning, organizing, actuating, and controlling. This integration contributes to the formation of a positive image, increased customer trust, and business sustainability amid competitive market competition.